Discretionary Accruals: Detecting the Quality of Earnings Using Corporate Governance, Firm Size and Leverage - Melasari Melasari; Yeni Widyanti (International Journal of Accounting and Management Research, 2023)
This research is designed to explain the influence of leverage, size and corporate governance proxied by the audit committee independent commissioners on earnings quality as measured using discretionary accruals directly and through the moderating variable family ownership. Data was obtained from the financial reports of companies that met the sample criteria of 644 manufacturing companies in 2019-2022. The data analysis method uses descriptive analysis. The results showed that each variable has a different effect, such as the audit committee and leverage variables, there is no effect on earnings quality, this shows that the presence or absence of an audit committee and high or low does not encourage companies to make discretionary accruals, while the independent commissioner variable has a negative and significant effect on earnings quality, then company size has a positive effect on earnings quality. This research provides insight into the importance of corporate governance and its practical implications to assist company stakeholders in optimising corporate governance policies and earnings management strategies.